O capital cultural do estudante da EAD na educação superior brasileira - Zeni, Marindia (2016)
This study aimed to contribute to the construction of knowledge about distance education mode in Brazilian higher education answering the folowing question: do the predominant profile cultural capital of the students of distance education modeis analogous to the student's classroom mode and suitable for distance education mode? Therefore, we used a combination of these methods; literature, document analysis, statistical method and comparative method. To analyze the cultural capital of distance education student and ascertain to what extent the distance learning student profile was similar to that of classroom students were compared the respondents of Enade 2009 besides three specific courses: Administration (graduating in (2009), Accounting (graduating in 2009) and Pedagogy(graduating in 2008), chosen because they have the appropriate number of students required for statistical comparisons and the Pedagogy course (last year), and the number of students, as a course of teacher training, an area of great representation in distance education, not assessed Enade in 2009. The focus of the study was the "Student Survey" prior to their participation in Enade, in particular this four questions: monthly household income; mother graduation; training in high school and student work situation. In general, the distance learning student is poorer, work more, he attended high school in the public school and his mother has low education. Relating this information with the cultural capital of Pierre Bourdieu observes that the student of distance education Brazilian higher level has lower level of cultural capital in comparison with the cultura capital level of student classroom mode. Also, the features raised as to distance education student allow consider that the public distance education in Brazil is not the most suitable for this type of education due to, according to Maia and Mattar (2007), Moore and Kearsley (2008) and Silva (2012), the distance education student should be autonomous, digitally fluent and organized, features generally found in sections of society with a higher level of cultural capital. Thus, the work indicates that the target group top-level distance education in Brazil is uneven when compared to the student classroom mode, being the holder of a lower cultural capital when set against the student classroom mode and requiring thus a specialized look. Furthermore, compare modalities or courses only through the performance of students in Enade without considering the cultural capital of the students, will lead to misunderstanding, especially if comparisons occur between distance education and classroom arrangements, because as evidenced by the study, distance education students have cultural capital lower than classroom mode students and, as evidenced by Bourdieu, the level of cultural student capital is great influencer in your success or failure in school, in this way, it is not appropriate to treat or compare different as if they were equal.